Development of Educational Augmented Reality Game as English Language Learning Media with Character Education Values - Elinda Umisara; Alim Mutaqin; Siti Ulin Nuril Hidayah (Wahana, 2023)
The primary objective of this research is to create an educational Augmented Reality game as a learning tool. This media can be accessed on Android smartphones and developed using the Unity application. The study adopts a research and development (R&D) approach, following the ADDIE development model, which includes Analysis, Design, Development, Implementation, and Evaluation stages. The validation process involves assessments by subject matter experts, media experts, and language experts, resulting in a highly favorable rating with a validity percentage of 96.33 percent for the learning media. To conduct the testing, 15 fifth-grade Elementary School students are selected using purposive sampling. The students’ responses to the educational game, focusing on the English language topic "part of the human body" and incorporating Augmented Reality, were overwhelmingly positive, with a percentage of  greater equal to 70 percent for each assessment indicator.